2020
DOI: 10.1111/jch.14011
|View full text |Cite
|
Sign up to set email alerts
|

Randomized elimination and prolongation of ACE inhibitors and ARBs in coronavirus 2019 (REPLACE COVID) Trial Protocol

Abstract: Clinical Trial Registration Number: clinicaltrials.gov NCT04338009 | 1781 COHEN Et al. 1 | INTRODUC TI ON Since its emergence in December 2019, the coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has had a devastating global health impact. 1 COVID-19 is associated with a high incidence of multiorgan dysfunction and mortality. 2,3 Accordingly, there has been an extraordinary response by the international research community to quickly develop trials to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
0
18
0
1
Order By: Relevance
“…The results showed that ramipril had no impact on the incidence or severity of COVID-19, which is in line with our results. Additional protocols from RCTs have also been published, and their results deserve attention [ 40 42 ]. Thus, our systematic review based on currently available large cohort studies will have clinical value until the results of additional well-designed RCTs with large sample sizes become available.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that ramipril had no impact on the incidence or severity of COVID-19, which is in line with our results. Additional protocols from RCTs have also been published, and their results deserve attention [ 40 42 ]. Thus, our systematic review based on currently available large cohort studies will have clinical value until the results of additional well-designed RCTs with large sample sizes become available.…”
Section: Discussionmentioning
confidence: 99%
“…An independent data safety monitoring board was assembled to provide independent oversight of the trial. Details of the rationale and trial design have been previously described 17 and additional details are included in appendix 2 (pp 2–6 ).…”
Section: Methodsmentioning
confidence: 99%
“…The first randomised control trials concerning this topic are currently ongoing, the results of which will be the next important step in clarifying the role of ACEi/ARBs in acute COVID-19 illness. [23][24][25][26][27] Regular ACEi/ARB use in our study was associated with worsened indicators of morbidity. It is possible that this is attributable to the large number of our cohort that had their ACEi/ARBs omitted during admission, an intervention that we find to be strongly associated with poorer outcomes.…”
Section: Comparisons With the Literaturementioning
confidence: 96%